1999
DOI: 10.1086/515117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Case Definitions of Influenza: Detailed Investigation of Patients During the 1995‐1996 Epidemic in France

Abstract: Using clinical predictors, we evaluated clinical case definitions of influenza during the 1995-1996 outbreak in France. Thirty-five general practitioners collected virological specimens and clinical data. Predictors of influenza virus infection were selected with logistic regression models. The results varied with the influenza virus subtype: temperature of >38.2 degrees C, stiffness or myalgia, rhinorrhea, and cough were predictive of influenza A/H3N2, whereas fatigue, lacrimation or conjunctival injection, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
116
5
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 35 publications
11
116
5
3
Order By: Relevance
“…Specifically, the detection of influenza infection presenting with both fever and cough was observed to have sensitivities ranging between 64 and 86%, specificities between 55 and 67%, and PPVs ranging between 48 and 87% [5,6,19,20]. This contrasts other studies which reported that no clinical signs or symptoms are specific for influenza virus infection [21,22]. The present study indicates that the clinical diagnosis of influenza, based on the combined presence of fever and cough, is difficult among children in everyday clinical practice.…”
Section: Discussioncontrasting
confidence: 64%
“…Specifically, the detection of influenza infection presenting with both fever and cough was observed to have sensitivities ranging between 64 and 86%, specificities between 55 and 67%, and PPVs ranging between 48 and 87% [5,6,19,20]. This contrasts other studies which reported that no clinical signs or symptoms are specific for influenza virus infection [21,22]. The present study indicates that the clinical diagnosis of influenza, based on the combined presence of fever and cough, is difficult among children in everyday clinical practice.…”
Section: Discussioncontrasting
confidence: 64%
“…In outpatient studies, many recruitment strategies involve evaluating patients when they report ILI symptoms, such as fever and respiratory symptoms. [2][3][4][5][6] Not surprisingly, these studies observed high rates of fever and respiratory symptoms. Several reports have documented shortcomings of the definition of ILI in long-term care facilities, specifically because many patients did not have documented fever.…”
Section: Discussionmentioning
confidence: 86%
“…The difficulties of identifying influenza virus infection on the basis of clinical characteristics have been well described for outpatients, [2][3][4][5][6][7] patients in the emergency department, 8,9 and residents of nursing homes. 10 There are fewer recent data regarding the clinical presentation of hospitalized patients with influenza.…”
Section: Infect Control Hosp Epidemiolmentioning
confidence: 99%
“…Indeed, 38% of contacts classified as secondary patients did not report a fever. In patients consulting physicians for a respiratory illness during an influenza epidemic period, the relative risk that fever >37.8°C is associated with an influenza diagnosis was 2.5 in one study (4.6 for influenza A [H3N2] specifically), 20 and 3.3 in another. 16 However, syndromes associated with true influenza infection do not necessarily always include fever.…”
Section: Strengths and Limitationsmentioning
confidence: 91%